2004
DOI: 10.2166/wst.2004.0828
|View full text |Cite
|
Sign up to set email alerts
|

Sand filter clogging by septic tank effluent

Abstract: The aim of this study was to characterise conditions and factors affecting fine sand clogging by septic tank effluent on the basis of physical modelling. The physical model consisted of 12 sand columns dosed with sewage from one household (5 persons), preliminary treated in a septic tank. Hydraulic loadings of the sand filters were equal to 82 mm/d. The mean discharge from sand columns, measured as the effluent volume collected during 10 minutes, decreased significantly over the experiment period from 34 cm3/m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
21
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(24 citation statements)
references
References 0 publications
3
21
0
Order By: Relevance
“…[2] or [3] has shown that strong biofilm formation, eventually in conjunction with entrapped metabolic gasses may finally cause biological clogging by reducing the void volume and in consequence the soil permeability. [48] found same results for biological clogging in sand filters. The same trend of a decreasing soil permeability was observed in the sand of the SSC (Fig.…”
Section: Effect Influence Of Biofilm Formation On Horizontal Water Flowsupporting
confidence: 70%
“…[2] or [3] has shown that strong biofilm formation, eventually in conjunction with entrapped metabolic gasses may finally cause biological clogging by reducing the void volume and in consequence the soil permeability. [48] found same results for biological clogging in sand filters. The same trend of a decreasing soil permeability was observed in the sand of the SSC (Fig.…”
Section: Effect Influence Of Biofilm Formation On Horizontal Water Flowsupporting
confidence: 70%
“…The reason for proposing the anti-sized arrangement is based on the following facts, (1) the most important factor to cause clogging is the filtration of SS that congests the void space of bed media (Blazejewski and Murat-Blazejewska, 1997;Langergraber et al, 2002); (2) clogging takes place mainly in the top layer of the media, and the thickness of clogging layer has been reported to be in the range of 0-2.5 cm (Spychala and Blazejewski, 2002), 0-10 cm (Nguyen, 2000), 0-15 cm (Blazejewski and Murat-Blazejewska, 1997) and 0-30 cm (Kadlec and Watson, 1993); and (3) relatively higher organic loading and more rapid decomposition of carbonaceous pollutants in the top layer leads to considerable biomass production that also contributes to clogging according to Scholz and Xu (2002). The anti-sized medium arrangement allows the top layer of coarse gravels to remove a large amount of suspended solids, while smaller sized gravels in the lower layers further polishes the effluent.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the growth of plant rhizomes and roots, chemical precipitation and deposition, and the formation and accumulation of humic substances may also be part of the cause. Reviews of the clogging phenomenon in the reed beds are recently reported by Langergraber et al (2002) and Spychala and Blazejewski (2002). Ideally reed beds should be able to operate under a broad range of hydraulic and organic loadings while high treatment efficiency is maintained.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Clogging reduces the infiltration capacity as well as the oxygen supply into a wetland system, leading to an extremely fast failure of the treatment performance. Although several means of mitigating clogging have been suggested (Platzer and Mauch, 1997;Spychala and Blazejewski, 2002;Langergraber et al, 2003) the problem still persists. Therefore, in order to counteract clogging, the concept of "anti-sized" media arrangement was introduced, leading to the development of the so called "anti-sized" CWs (Zhao et al, 2004b(Zhao et al, , 2005.…”
Section: 'Anti-sized' Constructed Wetland Systemsmentioning
confidence: 99%